Green approach towards size controlled synthesis of biocompatible antibacterial metal nanoparticles in aqueous phase using lysozyme - Kumar, Umesh; Ranjan, Amaresh K.; Sharan, Chandrashekhar; Hardikar, Anandwardhan A.; Pundle, Archana; Poddar, Pankaj (Current Nanoscience, 2012)
Inspired by array of proteins present in nature, we choose lysozyme (hen egg protein) as a model system to synthesize nanoparticles of noble metals to understand the mechanism of interaction as well as to use them for potential applications such as potent antibacterial agents. Lysozyme is a very well studied biomolecule containing aromatic amino acids like tryptophan and tyrosine. Tyrosine has phenoxy group which is considered to be responsible for interacting with the metal ions. Lysozyme can be suitably modified by treatment with N-bromosuccinimide/N-acetylimidazole to obtain tight control over size distribution of nanoparticles. Here we report the direct synthesis of nanocrystals of gold and silver at controlled pH and light conditions without using any known reducing agents. Out of these, synthesis of gold nanoparticles is assisted by the presence of low concentration of Ag+ ions through the galvanic exchange. It is remarkable to note that the structure of protein is not changed drastically as seen by the FTIR studies. As-synthesized lysozyme capped nanoparticles prepared by this method are biocompatible and retain antibacterial property.
Keywords: Antibacterial; Biocompatible; Gold; lysozyme; Nanoparticles; Silver